Vegetation analysis of hill forest in Ulu Muda Forest Reserve, Baling, Kedah - Ya'akub, Khairul Na'im; Abd. Kudus, Kamziah; Salleh @ Japri, Mohd Nazre; Abd. Ghani, Awang Noor; Ibrahim, Faridah Hanum (Contemporary Research Centre, 2013)
This paper emphasize on the quantitative analysis of trees of unlogged hill forest in Ulu Muda Forest Reserve. Two plots of 1-hectare size were established within the forest area and divided to 100 10x10m quadrates. Only trees with dbh more or equal to 5 cm been observed. The species name, dbh and tree height were recorded from the trees. A total of 1825 of individual trees were observed in the two 1-hectare plots with 43 family and 236 species. The most dominant and diverse species is Mallotus kingii with 195 individuals in the 2ha plot, total basal area 3.17m2, relative basal area 5.87% and IVI 22.99. While the family Euphorbiaceae has the highest FVI (60.73). The most diverse plot is plot 2 with 976 individuals and 179 species.